Psychiatry and the 'Gay Holocaust' – the lessons of Jill Soloway's Transparent. (December 2016) - Robertson, Michael D; Light, Edwina; Walter, Garry; Lipworth, Wendy
Objective: We aim to consider issues relevant to psychiatry raised by the television series, Transparent . Conclusions: Psychiatry's disturbing history regarding the lesbian, gay, bisexual, transgender and intersex (LGBTI) community shares many aspects with the group's persecution by the National Socialist regime in Germany. The medicalised 'otherness' conferred on LGBTI patients, latent homophobia and transphobia, and lack of culturally sensitive clinical services for these people represent a major ethical challenge for modern Australasian psychiatry.